UPAYA MENINGKATKAN HASIL BELAJAR TEMA 9 BENDA-BENDA DI SEKITAR CONTEXTUAL TEACHING AND LEARNING KELAS 5 SD NEGERI 4 NGEMBAK SEMESTER 2KITA MELALUI MODEL PEMBELAJARAN - Karolina Ari Putri Agnestasya; Ervina Eka Subekti; Kuswandari Kuswandari (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: This study was conducted on grade 5 students with the theme of 9 Objects Around Us, in the learning process teachers still use lecture methods, thus impacting the way students think and the learning outcomes of 55% students have not reached KKM. To fix the problem and will improve student learning outcomes, learning is done using contextual teaching and learning model. The type of research conducted is Class Action Research. The subject of the study was a grade 5 student at SD Negeri 4 Ngembak. Data retrieval instruments using observation sheets and test questions. From the results of the research that has been done found that learning using contextual teaching and learning model can improve the results of learning the theme of 9 Objects Around Us in grade 5 students of SD Negeri 4 Ngembak Semester 2 school year 2020-2021. This can be proven by the result of the percentage of students' complete learning outcomes increased, starting in the initial condition of 6 students (40%) increased in cycle I 8 students (54%) increase in cycle II 10 students (66%) improvement in cycle III 13 students (88%). The advice that the authors can propose in this study is that teachers can use contextual teaching and learning models as guidelines to improve students' learning outcomes on the learning theme of 9 Objects Around Us. Keywords: Learning Outcomes, Learning Models, Contextual Teaching And Learning Abstrak: Penelitian ini dilakukan pada siswa kelas 5 tema 9 Benda-Benda Di Sekitar Kita, pada proses pembelajaran guru masih menggunakan metode ceramah, sehingga berdampak pada cara berpikir siswa serta hasil belajar siswa 55% belum mencapai KKM. Untuk memperbaiki permasalahan tersebut dan akan meningkatan hasil belajar siswa maka dilakukan pembelajaran menggunakan model pembelajaran Contextual Teaching And Learning. Jenis penelitian yang dilakukan adalah Penelitian Tindakan Kelas. Subjek penelitian yaitu siswa kelas 5 SD Negeri 4 Ngembak. Instrumen pengambilan data menggunakan lembar observasi dan soal tes. Dari hasil penelitian yang sudah dilakukan ditemukan hasil bahwa pembelajaran dengan menggunakan model pembelajaran Contextual Teaching And Learning dapat meningkatkan hasil belajar tema 9 Benda-benda di Sekitar Kita pada siswa kelas 5 SD Negeri 4 Ngembak Semester 2 tahun ajaran 2020-2021. Hal ini dapat dibuktikan dengan hasil persentase hasil belajar siswa yang tuntas meningkat, terjadi mulai pada kondisi awal 6 siswa (40%) meningkat pada siklus I 8 siswa (54%) peningkatan pada siklus II 10 siswa (66%) peningkatan pada siklus III 13 siswa (88%). Saran yang dapat penulis ajukan pada penelitian ini yaitu guru dapat menggunakan model pembelajaran Contextual Teaching And Learning sebagai pedoman untuk meningkatkan hasil belajar siswa pada pembelajaran tema 9 Benda-benda di Sekitar Kita. Kata Kunci: Hasil Belajar, Model Pembelajaran, Contextual Teaching And Learning